Research on overcharge thermal runaway behavior analysis and early warning algorithm of ternary lithium battery pack - He, Xingfeng; Du, Jianhua; Yang, Shizhi; Cao, Xin; Qu, Chang; Ou, Yingjie; Wang, Jiabin; Xiong, Leji; Tu, Ran (Journal of applied electrochemistry, 2025)
During the charging process, lithium-ion batteries may experience thermal runaway due to the failure of overcharging protection mechanisms, posing a significant fire hazard. This work by analyzing the evolution of surface temperature, space temperature, and voltage of ternary lithium battery pack under different overcharging rates, a three-level early warning algorithm and device for thermal runaway of ternary lithium battery pack were developed. The results revealed that the entire thermal runaway process can be divided into three stages: early, middle, and late, based on the variations in batteries’ physical morphology, voltage, and temperature. Under identical initial conditions, the internal chemical reactions within the battery became more intense with the increasing charging rate, resulting in an earlier occurrence of thermal runaway. Ultimately, through testing and validation, the designed three-level warning algorithm proved capable of accurately assessing overcharging conditions in lithium batteries and issuing warnings in the early stages of thermal runaway. This work provided crucial references for enhancing the monitoring and warning capabilities of the battery management system. Graphical abstract